Intestinal microbiology and metabolomics of streptozotocin-induced type 2 diabetes mice by polysaccharide from Cardamine violifolia - Zimu Zhang; Qing Zhang; XiuFang Huang; Kai Luo (Journal of Functional Foods, 2022)
Cardamine violifolia polysaccharide (CVP) has been studied mainly for structural analysis and in vitro activity. The present study showed that CVP supplementation was effective in enhancing the production of N-Oleoylethanolamin and improving the content of campesterol and stigmasterol in the Steroid biosynthesis - Mus musculus metabolic pathway. The genus levels of Ruminococcaceae_UCG-014 genus, Lactobacillus genus, were significantly increased in the intestine of mice after CVP infusion. Importantly, CVP had a protective effect on the intestinal microbiota of mice, which may result from the increase in short-chain fatty acid-producing bacteria of the genera Ruminococcaceae and Lactobacillus. The therapeutic effect of CVP in STZ-induced type 2 diabetic mice may be achieved by modulating the structure of the intestinal microbiota and regulating the Steroid biosynthesis - Mus musculus metabolic pathway, and CVP is expected to be a potential food for the treatment and prevention of type 2 diabetes.